(untitled) (London, 2015)
A Guide to Professional Doctorates in Business and Management has been written by a team of experts with experience of the challenges faced in both studying for and supervising professional doctorates in business and management. Inside they address the key issues faced, in particular how these courses differ from a traditional PhD, and the different skills and approach needed for success.
Keywords: Industrial management,Quản trị công nghiệp; Study and Teaching (Higher),Dạy và học (Cao học)